DEVELOPMENT OF A COMPETENCY-BASED EVALUATION MODEL TO MEASURE SKILL IMPROVEMENT IN TECHNICAL AGRICULTURAL TRAINING PARTICIPANTS - amal, Andi; Syahrul; Purnamawati (Jurnal Vokasi Keteknikan, 2026)
Evaluation in technical agricultural training plays a strategic role in ensuring the achievement of vocational education goals, particularly the comprehensive development of participants’ competencies encompassing knowledge, skills, and work attitudes. However, current evaluation practices in agricultural training are still predominantly focused on cognitive assessment through written tests, which inadequately represent participants’ technical skills. This article aims to describe the development of a competency-based evaluation model designed to measure skill improvement in technical agricultural training participants. The study employed a Research and Development approach, including needs analysis, model design, expert validation, limited trials, and analysis of practicality and effectiveness. The development resulted in the TERAPAN Evaluation Model, consisting of five stages: Review, Design, Action, Projection, and Conclusion. The instruments demonstrated strong validity (Aiken’s V > 0.80) and reliability. Effectiveness was evidenced by a knowledge improvement N-Gain score of 0.8013 (high category), average skill score of 81.36 (very skillful), and average attitude score of 82.43 (very good). The overall average achievement was 81.69 (very good category). The model is therefore feasible as a competency-based evaluation guideline for agricultural technical training.